If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7n + 23 = -3 + -5(n + -8) Reorder the terms: 23 + -7n = -3 + -5(n + -8) Reorder the terms: 23 + -7n = -3 + -5(-8 + n) 23 + -7n = -3 + (-8 * -5 + n * -5) 23 + -7n = -3 + (40 + -5n) Combine like terms: -3 + 40 = 37 23 + -7n = 37 + -5n Solving 23 + -7n = 37 + -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. 23 + -7n + 5n = 37 + -5n + 5n Combine like terms: -7n + 5n = -2n 23 + -2n = 37 + -5n + 5n Combine like terms: -5n + 5n = 0 23 + -2n = 37 + 0 23 + -2n = 37 Add '-23' to each side of the equation. 23 + -23 + -2n = 37 + -23 Combine like terms: 23 + -23 = 0 0 + -2n = 37 + -23 -2n = 37 + -23 Combine like terms: 37 + -23 = 14 -2n = 14 Divide each side by '-2'. n = -7 Simplifying n = -7
| x-5+7b=28 | | B=33+-7b | | 2.1*1= | | 3/240=705/x | | 5.3=8.1-0.4x | | Un=4n | | 705/240=3/x | | -5v-8v=7+9 | | 190=10x+2(1.5x) | | 3275/1.5 | | 200-0.45x=650 | | 4+5x=6x-3 | | 5/7(14/3) | | 7(8+3x)=-140 | | cos(x+45)+cos(x-45)=2 | | 2x-11=2x+1 | | 5x=-x+34 | | 0.007(8-k)+0.06(k-1)=1 | | 8x^2+35x=25 | | 7x-7-x=4 | | -7/1*1/7- | | (y^2-3)(9y^2-7y+7)= | | -10+6x-5x=0 | | .4h+1=16+1.1h | | 2(x-1)=3(11-x) | | 0.128+0.035v=-0.072v+0.235 | | 45=-5(6-3z) | | 1.5p=1.25p-4 | | 13y-21=18 | | -3.1x+9.2=2.06-1.15x | | 5(y+6)=55 | | -7u=-6 |